Student involvement in radical politics: a study in Sultan Idris University of Education (UPSI) - Boyman, Siti Noranizahhafizah; Mohammed Shaed, Maslina; Mohd Isa, Nur Ayuni (Science and Engineering Research Support Society, 2020)
This study examines radical political involvement among students at Sultan Idris University of Education (UPSI). This is important to be studied because UPSI as an institution generates intellectuals who will educate the present and future generations. The main objective of this study was to examine the level of student involvement in politics and the factors that influenced radical politics. To obtain the required information, this study used quantitative and qualitative approaches. For the quantitative aspect, the data were collected through the survey research method. This study involved 405 respondents. For the qualitative aspect, in-depth interview techniques were used. Four informants were interviewed to answer in detail regarding the motivating factors for being involved in radical politics. The findings indicated that the political pursuits of students in UPSI were at a low level. In addition, the findings depicted that the highest factors driving students into radical politics were weak government administration, media influence, and dissatisfaction with existing policies. Finally, the study found that UPSI students had made a paradigm shift in terms of their views of radical politics, which would bring a positive impact on the country. Thus, this will affect the democratic space in Malaysia. However, the students must possess a clear understanding of radical politics to ensure the sustainability of security and prosperity in Malaysia is not threatened.